CONCEPTS OF DEVELOPMENT OF URBAN AREAS IN DEVELOPING COUNTRIES - A. Z. Al-Fahad (Вестник университета, 2016)
In this article the problems of development of urban areas from the point of view of economy, the main tendencies of city building, the main criteria of sustainable economic development of urban areas and major factors interfering effective complex development of urban areas are researched.